A review: Research on corrosive sulphur in electrical power equipment. (12th October 2021) - Yuan, Yuan; Gao, Xue; Zhou, Jiang; Liu, Guoyong; Kuang, Xiongwei; Yang, Lijun; Liao, Ruijin
Abstract: Corrosive sulphur has been commonly regarded as an enormous threat to electrical power equipment in recent decades. Cuprous sulphide (Cu2 S) deposition on the insulating oil and paper insulation caused by sulphur corrosion will bring about insulation deteriorations or failures in power transformers and shunt reactors. A large number of experiments have been carried out to investigate sulphur corrosion and some measures have been come up to solve this issue such as replacement of insulating oil, chemical removal of corrosive sulphur and the addition of passivator and so on. However, there has not been a perfect method to work out this problem completely, and the phenomenon of sulphur corrosion still occurs. This paper intends to provide thorough information of corrosive sulphur in power equipment and give detailed explanations about its corrosion mechanism, hazards and control measures, which is supposed to offer a reference for subsequent researchers.